Legal Guarantees to Protect Family Interests - a Comparative Analytical Study - - Al-Dalawi, Assist. Prof. Dr. Bamo Parvez Khan; Hussein, Assist. Prof. Dr. Ismail Namiq (Journal of Legal and Political Studies, 2018)
The interests of a family can be defined as the benefits which lead to the continuum of the family. It is inherent in keeping away the harms that may disturb the familial bondages and atmosphere and it threatens family structure. These benefits and harms have a material value, but others have mental values. In order to protect both values, some legal insurance have been set which are affected by the type of familial interests and protection, in addition to the effect of the current legal system of the society. We have underlined the family interests in this study first, then we have shown the legal insurances which are set to protect these interests.
Keywords: familial interests; Protection; Harms; legal insurances